2023
DOI: 10.3390/biomedicines11020586
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Hepatocellular Carcinoma Surveillance Focusing on Non-Cirrhotic NAFLD Patients: A Challenge for Physicians

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of liver disease worldwide and it ranges from simple steatosis to hepatocellular carcinoma (HCC). HCC represents the first liver tumor and the third source of cancer death. In the next few years, the prevalence of NAFLD and consequently of HCC is estimated to increase, becoming a major public health problem. The NAFLD-HCC shows several differences compared to other causes of chronic liver disease (CLD), including the higher percentage of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 218 publications
0
6
0
Order By: Relevance
“…Other proposed mechanisms of oncogenesis include lipid peroxidation (resulting in oxidative stress and free radical formation), and elevated levels of insulin + IGF-1 resulting in cellular proliferation. [10,11] Patients with MASLD and metabolic syndrome have been shown to possess a higher risk for HCC development in patients without cirrhosis than when compared to patients without cirrhosis with hepatotropic viral infection or alcohol use disorder. In fact, a 2014 study demonstrated that the leading etiology of noncirrhotic HCC was related to metabolic syndrome.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other proposed mechanisms of oncogenesis include lipid peroxidation (resulting in oxidative stress and free radical formation), and elevated levels of insulin + IGF-1 resulting in cellular proliferation. [10,11] Patients with MASLD and metabolic syndrome have been shown to possess a higher risk for HCC development in patients without cirrhosis than when compared to patients without cirrhosis with hepatotropic viral infection or alcohol use disorder. In fact, a 2014 study demonstrated that the leading etiology of noncirrhotic HCC was related to metabolic syndrome.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In fact, a 2014 study demonstrated that the leading etiology of noncirrhotic HCC was related to metabolic syndrome. [3,11] In addition, a study from 2018 revealed that the annual incidence of HCC in patients with MASLD without cirrhosis was about 0.08 per 1000 patients. Among MASLD-related HCC, the percentage of cases without underlying cirrhosis has ranged from 10% to 75%.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10–20% of HCC cases is attributable to MASLD ( 2 ), thus projecting the proportion of the annual incidence of the liver cancer worldwide and requiring a growing attention in surveillance programs ( 3 , 4 ). With the advances in antiviral therapies, MASLD-related HCC is becoming also the sixth most common tumor globally and the second indication for liver transplantation in the United States ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cardiovascular risk and the progression of liver fibrosis, the importance of MASLD diagnosis lies in the possibility of developing hepatocellular carcinoma without cirrhosis. These mechanisms are still unknown [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%